11 birthdays - Mass, Wendy, 1967- (New York : Scholastic Press, 2009)
After celebrating their first nine same-day birthdays together, Amanda and Leo, having fallen out on their tenth and not speaking to each other for the last year, prepare to celebrate their eleventh birthday separately but peculiar things begin to happen as the day of their birthday begins to repeat itself over and over again.
Keywords: Birthdays -- Juvenile fiction; Time -- Juvenile fiction; Friendship -- Juvenile fiction; Interpersonal relations -- Juvenile fiction